Keterbatasan vs Kesempatan: Analisis Akses dan Stigma Penyandang Disabilitas pada Pasar Kerja Formal - Utami, Yeski Putri; Afriyanti, Winda; Kamiilah, Aliyyah Najmah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Lack of access to formal labor market and social stigma towards people with disabilities often create negative stereotypes regarding their employability. This article aims to analyze the factors influencing the accessibility of formal sector employment for people with disabilities and to identify the impact of social stigma on their employment opportunities. The research method used is qualitative research through Systematic Literature Review (SLR) by reviewing various related studies from 2016-2024. The findings indicate that factors affecting access to formal employment for people with disabilities can be categorized into internal factors (including educational qualifications, skills, and self-confidence). Social stigma significantly affects employment opportunities, limiting the chances of people with disabilities in the formal labor market. Therefore, inclusive policies and shifts in societal perspective are needed to create a more disability-friendly labor market.